Data from the National Educational Panel Study (NEPS) in Germany: Educational Pathways of Students in Grade 5 and Higher. (7th February 2023) - Thums, Kathrin; Gehrer, Karin; Gnambs, Timo; Lockl, Kathrin; Nusser, Lena
The German National Educational Panel Study investigates individual competences and educational trajectories in a longitudinal multi-cohort study design. The third of the six starting cohorts focuses on paths through lower into upper secondary level and beyond. The representative sample includes about N = 6, 112 students from fifth grade attending regular or special schools. Students were initially sampled in 2010 and, subsequently, received follow-up interviews and competence tests each year resulting, as of yet, in a total of 12 measurement waves. Additionally, important context persons (i.e., parents, teachers, and heads of schools) were included in the assessment design. The longitudinal nature of the data provides rich opportunities for research on the development of competences through secondary school.